Reconstruction of Mobilities for Electrons and Holes in Semiconductors (Journal of Partial Differential Equations, 2020)
From a simplified approximate semiconductor model, we develop a 1-D identification problem to recover the mobilities for electrons and holes in semiconductors based on the LBIC technique, and cast it as an optimization problem. Its solution is defined by the minimal point of some objective functional. On this argumentation, we derive the gradient operator of objective functional and the necessary condition for the solution of inverse problem. Our result provides a numerical approach to reconstruct the mobilities for electrons and holes in semiconductors.
Keywords: LBIC technique; variational method; inversion